The intervention effect of exercise on the attention of patients with depression: a systematic review - Haijun Dong; Cong Liu; Man Qin (Frontiers in Psychology)
ObjectiveThis paper aims to systematically evaluate the intervention effect of exercise on the attention of patients with depression.MethodsThe randomized controlled trials of exercise intervention on the attention of patients with depression in six databases were retrieved by computer, and the quality of the included literature was evaluated by the PEDro scale. The meta-analysis, subgroup analysis, publication bias test, and sensitivity analysis were performed by Stata 17.0, and the quality of evidence was evaluated by GRADEpro.ResultsA total of 11 literature involving 924 patients with depression were included. The results showed that exercise could improve the attention of patients with depression (Hedge’s g = 0.17, p = 0.01), exercise intensity (p = 0.00) had a regulatory effect on the intervention effect, and exercise form (p = 0.77), exercise duration (p = 0.58) and exercise cycle (p = 0.66) had no regulatory effect on the intervention effect.ConclusionExercise can improve the attention of patients with depression, among which moderate intensity has the best effect. This study has been registered on the international prospective register of systematic reviews Prospero (CRD4202477699).